Enriching Primary Schooling in India - Gupta, N. K. (INDIAN EDUCATIONAL REVIEW, 2015)
The present book, that addresses the issues of primary schooling for the teachers and teacher educators, is altogether different from other books on the subject. The preface of the book itself sets a tone for the whole composition and describes how it is different in terms of its approach, novelty and cogency of thoughts, and touches the core issues and problems that coexist with the teaching learning process at the elementary level. The book seeks to posit and answer various queries that normally crop up in the field of primary education from time to time, despite sincere efforts being put by the state and central governments to resolve them and theconstitutional provisions in place starting from Article 45 of Indian constitution to Right to Education Act. The book also sets about the pragmatics for removing the hurdles in the area of primary education.